TEACHERS’ QUESTIONING STRATEGIES TO ELICIT STUDENTS’ VERBAL RESPONSES IN EFL CLASSES AT A SECONDARY SCHOOL - Sri Wuli Fitriati; Gabby Allen Vica Isfara; Novia Trisanti (University of Kuningan, 2017)
This article reports on a study aimed at exploring and examining English language teachers’ skills in questioning to enhance students’ verbal repsonses in EFL (English as a Foreign language) classes. This was a qualitative case study, employing discourse analysis, conducted in one junior high school in a town in Central Java Province, Indonesia. The research participants were two Indonesian teachers of English language. They taught Year Eight students in the academic year of 2015/2016. The data were collected from audio-video recordings, transcripts of the lessons, classroom observations notes, and teachers’ interviews. The transcriptions were analysed by using Wu’s taxonomy of questioning strategies (1993) as it gave a detailed categorization of teachers’ questions to stimulate students’ verbal responses. The findings showed that the teachers used mostly four questioning strategies. The first teacher often applied decomposition strategy where the initial question was elaborated into some questions, while the second teacher tended to use repetition strategy. This study has shown that teachers’ questioning skills is crucial to successfully make students engaged in the classroom interaction, enhance students’ verbal responses, and lead to the comprehension of the lesson. Therefore, it is suggested that teachers should be more aware of their questioning skills to assist students achieve better proficiency in the English language. Keywords: Teachers’ questioning strategies, students’ verbal responses, EFL classes, classroom discourse analysis